Nonnative English-Speaking Students’ Lived Learning Experiences With MOOCs in a Regular College Classroom - Cho, Moon-Heum; Byun, Moonkyoung (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
The goal of this study was to gain in-depth understanding about nonnative English-speaking students’ lived experiences with massive open online courses (MOOCs) in a regular college classroom. Phenomenological methodology was used to examine those experiences in 24 Korean college students. Individual interviews, an open-ended online survey, observation notes, online weekly journal entries, and social media constituted the data sources. Findings show that students’ lived experiences included (a) wonder and interest, (b) novel learning and teaching practices, (c) preference for video style, (d) learning strategies, (e) motivation to learn, and (f) need for face-to-face interaction. Implications for integrating a MOOC in to a regular college course are also presented.